Stressing the Cardiopulmonary Vascular System: The Role of Echocardiography - Rudski, Lawrence G.; Gargani, Luna; Armstrong, William F.; Lancellotti, Patrizio; Lester, Steven J.; Grünig, Ekkehard; D'Alto, Michele; Åström Aneq, Meriam; Ferrara, Francesco; Saggar, Rajeev; Saggar, Rajan; Naeije, Robert; et al. (Journal of the American Society of Echocardiography, 2018)
The cardiopulmonary vascular system represents a key determinant of prognosis in several cardiorespiratory diseases. Although right heart catheterization is considered the gold standard for assessing pulmonary hemodynamics, a comprehensive noninvasive evaluation including left and right ventricular reserve and function and cardiopulmonary interactions remains highly attractive. Stress echocardiography is crucial in the evaluation of many cardiac conditions, typically coronary artery disease but also heart failure and valvular heart disease. In stress echocardiographic applications beyond coronary artery disease, the assessment of the cardiopulmonary vascular system is a cornerstone. The possibility of coupling the left and right ventricles with the pulmonary circuit during stress can provide significant insight into cardiopulmonary physiology in healthy and diseased subjects, can support the diagnosis of the etiology of pulmonary hypertension and other conditions, and can offer valuable prognostic information. In this state-of-the-art document, the topic of stress echocardiography applied to the cardiopulmonary vascular system is thoroughly addressed, from pathophysiology to different stress modalities and echocardiographic parameters, from clinical applications to limitations and future directions. •The right heart and pulmonary circulation play a key role in cardiorespiratory diseases.•The cardiopulmonary vascular system can be assessed at rest and during exercise by echo.•This evaluation allows a significant insight into cardiopulmonary physiology.•It also helps establish the etiology of pulmonary hypertension and other conditions.•The cardiopulmonary vascular system behavior provides significant prognostic information.